Movimento indígena no Médio Solimões: lideranças, organização e redes de diálogos e lutas coletivas para seguridade de seus direitos (1980- 2000) - Santos, Fábio Pereira dos (2024)
This work aims to contextualize and analyze the organization, paths of struggle, challenges, and achievements of the indigenous movement in the Middle Solimões region through the testimony of indigenous leaders and indigenists, within a historical timeframe from 1980 to 2000. During these highlighted years, various stages of the process of organization, legitimization, and realization of indigenous struggles were experienced. The nature of this research is grounded in a bibliographic approach, which involves the search and analysis of diverse literature, including books, articles, periodicals, and magazines, along with a field research component that values the oral history of the interviewees. The research objective is to listen to the accounts of indigenous leaders, indigenists, and other protagonists of the time to understand the formation and consolidation of the indigenous movement in the Middle Solimões region. The focus is on identifying the historical process of organization of this movement, investigating and understanding the path that led to its formation and strengthening.